A review of the Cladocera in Basrah, Iraq - Ajeel, Shaker G. (Iraqi Journal of Aquaculture, 2023)
Sixty-five species of freshwater Cladocera belong to twenty-two Genera are reported from Basrah city, based on 15 studies mentioned the species of Cladocera in addition to seven other studies reported only density of Cladocera group. The maximum density of Cladocera was 91225 (ind./m3) recording at Shatt Al-Arab- Al-Hartha region.